Co-regulation of catechins biosynthesis responses to temperature changes by shoot growth and catechin related gene expression in tea plants (Camellia sinensis L.). Issue 2 (4th March 2021) - Xiang, Ping; Wilson, Iain W.; Huang, Jiaxin; Zhu, Qiufang; Tan, Meng; Lu, Jing; Liu, Jianghong; Gao, Shuilian; Zheng, Shizhong; Lin, Dongyi; Zhang, Yue; Lin, Jinke
ABSTRACT: Catechins are the major compounds in tea ( Camellia sinenesis L.) and are responsible for its sensory qualities and health benefits. The study investigated the response of catechins biosynthesis to temperature changes in the controlled conditions and the possible mechanisms. The low-temperature treatment inhibited the growth of young shoots, suppressed the expression of catechins biosynthesis-related genes (except CsCHS3, CsDFR2, CsLAR2 ), and decreased the content of total esterified catechins but increased the content of total non-esterified catechins in tea plants. When the temperature increased from 15°C to 30°C, the young shoots grew faster, and the contents of total catechins, total esterified catechins and epigallocatechin gallate in tea plants increased by 87.7%, 92.5% and 53.6%, respectively. Meanwhile, the expression of growth-related genes was upregulated in the higher temperature treatment and was consistent with the response of catechins biosynthesis-related genes to temperature. The positive correlation and the cubic function (R 2  > 90%) were noted between the growth of young shoots and catechins content. In brief, the response of catechins biosynthesis to temperature changes coordinately regulated by shoot growth and catechins genes expression of tea plants. Our findings provide the reference for improving tea quality by increasing its catechin contents.